Characterization of morphological traits and RAPD polymorphism in selected forms of Kentucky bluegrass (Poa pratensis L.) - Szenejko, Magdalena; Rogalski, Maciej (Biodiversity: Research and Conservation, 2015)
Measurements were taken of seven morphological characteristics of various forms of Poa pratensis, including ecotypes (12), cultivars (4), and breeding lines (2). Statistically significant differences relating to the average number and length of vegetative shoots and the leaf width of the forms studied were determined using Tukey’s HSD test. Evaluation of genetic polymorphism was carried out using the RAPD-PCR method. 18 primers were used for molecular analysis and 473 amplification products were obtained, in which high levels of polymorphism (84.2%) and specificity (63) were discovered. The mean value of Dice’s coefficient, the genetic similarity indicator, was about 0.7. These results indicate a significant genetic similarity between most of the forms of Poa pratensis studied. A correlation was also observed between genetic variation and phenotypic diversity of the studied forms of Poa pratensis. Convergence was found to occur between phenotype and genetic similarity among the forms. Only the dos01 468 ecotype showed discrepancies in the assessment of phenotypic and genomic variability.